Genetic and ore-forming ages of the Fe–P–(Ti) oxide deposits associated with mafic–ultramafic–carbonatite complexes in the Kuluketage block, NW China. Issue 7 (3rd October 2019) - Chen, W.; Lü, X. B.; Cao, X. F.; Yuan, Q.; Wang, X. D.
Abstract: During the past 50 years, many geological and ore-deposit investigations have led to the discovery of the Fe–P–(Ti)-oxide deposits associated with mafic–ultramafic–carbonatite complexes in the Kuluketage block, northeastern Tarim Craton. In this paper, we discuss the genetic and ore-forming ages, tectonic setting, and the genesis of these deposits (Kawuliuke, Qieganbulake and Duosike). LA-ICP-MS zircon U–Pb dating yielded a weighted mean 206 Pb/ 238 U ages of 811 ± 5 Ma, 811 ± 4 Ma, and 840 ± 5 Ma for Kawuliuke ore-bearing pyroxenite, Qieganbulake gabbro and Duosike ore-bearing pyroxenite, respectively. The CL images of the Kawuliuke apatite grains show core–rim structure, suggesting multi-phase crystallisation, whereas the apatite grains from Qieganbulake and Dusike deposits do not show any core–rim texture, suggesting a single-stage crystallisation. LA-ICP-MS apatite 207 Pb-corrected U–Pb dating provided weighted mean 206 Pb/ 238 U ages of 814 ± 21 Ma and 771 ± 8 Ma for the Kawuliuke ores, and 810 ± 7 Ma and 841 ± 7 Ma for Qieganbulake and Duosike ores, respectively. The core–rim texture in apatite by CL imaging as well as two different ore-forming ages in the core and rim of the apatite indicate two metallogenic events for the Kawuliuke deposit. The first metallogenic period was magmatic in origin, and the second period was hydrothermal in origin. The initial ore-forming age of the Kawuliuke Fe–P–Ti mineralisation was ca 814 Ma and the second one was ca 771 Ma. On the other hand, the ore-forming ages of the Qieganbulake and Duosike deposits were ca 810 Ma and ca 841 Ma, respectively. Qieganbulake and Duosike deposits were of magmatic origin. Combined with previous geochronological data and the research on the tectonic background, we infer that the Kawuliuke, Qieganbulake and Duosike Fe–P–(Ti)-oxide deposits were formed in a subduction-related tectonic setting and were the product of subduction-related magmatism.